Practicing Sustainable Agriculture for Meeting Demand of Quality Foods - Zainuri, Zainuri; Sjah, Taslim (Empiricism Journal, 2025)
It is appear that there is the limited understanding of how sustainable agricultural practices can be effectively linked to the production of quality foods that meet evolving market and consumer demands, as existing studies tend to address sustainability and food quality in isolation. This paper highlights the importance practicing sustainable agriculture and meeting demand of quality foods for the good of whole society. This study applied a secondary data collection method to identify pathways for meeting the demand for quality foods through the practice of sustainable agriculture, using a qualitative descriptive analysis supported by thematic synthesis of policy documents, scientific literature, and sectoral reports. The study found that Sustainable practices enhance soil fertility and structure, reduce chemical residues, and promote balanced nutrient cycling, which collectively improve the nutritional value and safety of food products. In addition, environmentally sound farming systems strengthen resilience to climate variability and reduce production risks, thereby supporting consistent food supply. From a socio-economic perspective, sustainable agriculture can increase farmers’ incomes through efficiency gains, reduced input costs, and access to premium markets for quality foods. The study highlighted that adopting sustainable agriculture is not only essential for environmental protection but also critical for ensuring the availability of high-quality foods that meet consumer expectations and support food security. Policy support, farmer capacity building, and market incentives are identified as key factors in accelerating the transition toward sustainable food systems. This study contributes by integrating sustainable agriculture practices with quality food demand through a systematic synthesis of secondary evidence, providing conceptual and policy-relevant insights to support the development of sustainable, quality-oriented food systems.